Competitive performance, training load and physiological responses during tapering in young swimmers - Toubekis, A. G.; Drosou, E.; Gourgoulis, V.; Thomaidis, S.; Douda, H.; Tokmakidis, S. P. (Journal of Human Kinetics, 2013)
The study examined the changes of training load and physiological parameters in relation to competitive performance during a period leading to a national championship. The training content of twelve swimmers (age: 14.2±1.3 yrs) was recorded four weeks before the national championship (two weeks of normal training and two weeks of the taper). The training load was calculated: i) by the swimmer`s session-RPE score (RPE-Load), ii) by the training intensity levels adjusted after a 7x200-m progressively increasing intensity test (LA-Load). Swimmers completed a 400- m submaximal intensity test, a 15 s tethered swimming and hand-grip strength measurements 34-35 (baseline: Test 1), 20-21 (before taper: Test 2) and 6-7 (Test 3) days before the national championship. Performance during the national championship was not significantly changed compared to season best (0.1±1.6%; 95% confidence limits: -0.9, 1.1%; Effect Size: 0.02, p=0.72) and compared to performance before the start of the two-week taper period (0.9±1.7%; 95% confidence limits: 0.3, 2.1%; Effect size: 0.12, p=0.09). No significant changes were observed in all measured physiological and performance related variables between Test 1, Test 2, and Test 3. Changes in RPE-Load (week-4 vs. week-1) were correlated with changes in performance (r=0.63, p=0.03) and the RPE-Load was correlated with the LALoad (r=0.80, p=0.01). The estimation of the session-RPE training load may be helpful for taper planning of young swimmers. Increasing the difference between the normal and last week of taper training load may facilitate performance improvements.